(untitled) (Revista Brasileira Multidisciplinar, 2014)
The concern with the entry and exit of veterinary antimicrobials in the environment is rising, taking into account the expressive increase of intensive systems of poultry farming. The presence of several classes of antimicrobials in poultry litter, material with a varying composition which is distributes over the floor of sheds, and that has been thrown in agricultural soil after prohibition of its use in animal feed, has contributed to increase the presence of these compounds in soil and surface water. Although Brazil is the third largest producer of chicken meat, only few studies that investigate the presence of these compounds in poultry litter and in the environment have been described. Considering these aspects, this paper aims to present a discussion about poultry litter as a source of antimicrobials to the environment, as well as levels of these compounds found in other matrices, based on a literature research performed between 1999 to 2013 in the databases Web of Science, SciFinder, and Scopus. Gaps in this knowledge area are pointed out as suggestions for future studies, which could provide tools to improve decision for treatment and/or final disposal of waste generated by poultry farming.